11Beta-Hydroxylase Deficiency and Other Syndromes of Mineralocorticoid Excess as a Rare Cause of Endocrine Hypertension - Melcescu, E.; Phillips, J.; Moll, G.; Subauste, J.; Koch, C. A. (Hormone and Metabolic Research, 2012)
Hypertension represents a major public and global health problem, most of which likely can be improved by lifestyle changes including changing dietary habits with less consumption of processed and preserved foods, which generally contain higher amounts of salt than freshly prepared food items. Among causes for endocrine hypertension are syndromes of mineralocorticoid excess. This group of mostly monogenic and acquired disorders typically causes hypertension through activation of the mineralocorticoid receptor either directly or indirectly via hormonal mediators and from overactive amiloride-sensitive epithelial sodium channels located in the distal tubule and collecting ducts of the kidneys. Apart from primary aldosteronism, mineralocorticoid excess can be caused by congenital adrenal hyperplasia (CAH) due to mutations of the 11beta-hydroxylase and 17alpha-hydroxylase genes, by inactivating mutations of the glucocorticoid receptor gene (Chrousos syndrome), endogenous hypercortisolism (Cushing’s syndrome), by mutations of the 11beta-hydroxysteroid dehydrogenase type 2 gene (apparent mineralocorticoid excess/AME) or licorice/carbenoxolone intake, mutations of the epithelial sodium channel genes (Liddle syndrome), mutations of the mineralocorticoid receptor gene (Geller syndrome), and by mutations in the WNK1, WNK4, KLHL3, CUL3 genes (pseudohypoaldosteronism type 2 or Gordon syndrome). Most of these conditions are treated by restricting dietary salt intake. However, some require special therapies including dexamethasone/hydrocortisone (CAH), spironolactone/eplerenone (AME), epithelial sodium channel inhibitors amiloride/triamterene (Liddle and Gordon syndrome), while in others spironolactone and MR antagonists may be contraindicated due to an abnormally structured MR (Geller syndrome). We here review the pathophysiology, diagnosis, and therapy of these rare conditions including the presentation of a patient with 11beta-hydroxylase deficiency.
Keywords: congenital adrenal hyperplasia; epithelial sodium channel; liddle syndrome; aldosterone; pseudohypoaldosteronism; Chrousos syndrome; low renin